Treatment of pretreated coal gasification wastewater (CGW) by magnetic polyacrylic anion exchange resin. Issue 2 (June 2016) - Hu, Xuewei; Chen, Kai; Lai, Xinke; Yao, Qi; Ji, Siping; Kaiser, Kevin
Abstract: A magnetic polyacrylic anion exchange resin, NDMP, was employed to treat the pretreated Lurgi coal gasification wastewater (CGW). The effects of some factors such as resin dosage, adsorption time and the CGW molecular weight distribution as well as resin recyclability on the COD removal by NDMP were investigated. An economic and effective condition for the treatment of CGW by NDMP resin was a pH of 10, resin concentration of 8.0 g/L and adsorption time of 10 min. The molecular weight distribution showed the COD of CGW was mainly concentrated on small organic molecules in the fraction MW < 500 Da, and both of small organic molecules and macromolecular organic substances can be effectively absorbed onto NDMP. A mixture of 1% NaCl and 1% NaOH was found to be highly efficient for the regeneration of NDMP resin. This study reveals the high efficiency and reusability of NDMP for removing the organic matter of coal gasification wastewater, and shows its great potential application in industrial wastewater.